2012
DOI: 10.1016/j.tplants.2012.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Role of phytohormones in insect-specific plant reactions

Abstract: The capacity to perceive and respond is integral to biological immune systems, but to what extent can plants specifically recognize and respond to insects? Recent findings suggest that plants possess surveillance systems that are able to detect general patterns of cellular damage as well as highly specific herbivore-associated cues. The jasmonate (JA) pathway has emerged as the major signaling cassette that integrates information perceived at the plant–insect interface into broad-spectrum defense responses. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
718
1
8

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 759 publications
(738 citation statements)
references
References 128 publications
(148 reference statements)
11
718
1
8
Order By: Relevance
“…JA is a key player in plant inducible defenses against chewing insects from a wide range of taxa, such as Lepidoptera, Diptera, Coleoptera, Thysanoptera, Homoptera and Heteroptera (Kessler and Baldwin 2002;Bostock 2005;Howe and Jander 2008;Verhage et al 2011;Erb et al 2012). Several studies have shown the important role of JA in BG-AG interactions (Erb et al 2008;Soler et al 2013;Fragoso et al 2014).…”
Section: Aboveground and Belowground Inducible Defenses-the Role Of Pmentioning
confidence: 99%
“…JA is a key player in plant inducible defenses against chewing insects from a wide range of taxa, such as Lepidoptera, Diptera, Coleoptera, Thysanoptera, Homoptera and Heteroptera (Kessler and Baldwin 2002;Bostock 2005;Howe and Jander 2008;Verhage et al 2011;Erb et al 2012). Several studies have shown the important role of JA in BG-AG interactions (Erb et al 2008;Soler et al 2013;Fragoso et al 2014).…”
Section: Aboveground and Belowground Inducible Defenses-the Role Of Pmentioning
confidence: 99%
“…Phytohormones, including JA, ethylene (ET), salicylic acid(SA), abscisic acid (ABA), auxin, cytokinins (CK), brassinosteroids (BR) and gibberllins (GB), have been reported to play important roles in both plant‐insect and plant‐microbe interactions (Erb et al ., 2012; Lazebnik et al ., 2014). These phytohormones function as signal transducers in plant‐induced defence pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Perception of herbivore induced elicitors and effectors by the membrane bound receptors activate the putative herbivore or damage-associated molecular patterns (HAMP or DAMP), some that are parallel to pathogen or microbe-associated molecular patterns (PAMP or MAMP), critical in basal or induced immune system [8][9][10]. Since most phloem-feeders cause minimal physical damage to the plant tissue, the resulting defense responses are similar to those associated with PAMP or MAMP and are recognized by pattern recognition receptors (PRRs) present on the surface of plant cells [3,8].…”
Section: Introductionmentioning
confidence: 99%
“…Since most phloem-feeders cause minimal physical damage to the plant tissue, the resulting defense responses are similar to those associated with PAMP or MAMP and are recognized by pattern recognition receptors (PRRs) present on the surface of plant cells [3,8]. Perception of phloem-feeding herbivores by R genes similar to disease resistance R proteins encodes a coiled coil nucleotide-binding leucine rich repeat (CC-NBS-LRR) protein [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%